Steps and other stories - Gregorio, Vanessa D.; Reyes, Isabelita O. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2014)
Steps and Other Stories is an undergraduate thesis divided into two parts. The first part is an analysis of the mother character in Philippine short stories in English from 1996-2008. By examining sixteen different short stories, qualities of the mother character and major patterns present in "mother stories" are determined. The second part of this thesis is a collection of short stories, all of which explore the different experiences of motherhood and mother-child relationships in a Filipino setting. The stories are entitled "Steps", "1:45pm at the Monumento Circle", "Mrs. de la Paz", "In Time", and "Nine Days", respectively.
Thesis (B.A. in Creative Writing)--University of the Philippines Diliman